Study of sand brick properties with partial replacement of rice husk as sand with ratio 10%, 20%, 30% - Ahmed Mohammed Gabir, Adham (2018)
Brick is widely used in construction and building material around the world. In this study, sand brick is prepared by adding a natural waste material which is rice husk. Disposal of agricultural waste material such as rice husk has constituted an environmental challenge, hence it can be turned into useful materials, the potential of using agriculture waste in civil engineering and building material have been investigated by various researchers. Cement is used as the binding material for rice husk and sand. In this study, a standard mix of 6:1 for sand cement ratio was used as standard control, while rice husks are added by using difference ratio 0%, 10%, 20%, and 30% of rice husk replaced with sand. The compressive strength and flexural strength of brick was tested at 7 days, and 28 days of water curing and air curing. The water absorption and density were tested at 7 days of water curing followed by 7 days of oven dried specimens. The mold sizes were used 210mm x 100mm x71mm. Two mixes were prepared in this research which are control mix and modified mix. Rice husk added in sand brick can be classified under lightweight brick. The main objective of this study is to investigate the optimum ratio of rice husk in sand brick. The use of rice husk in sand brick can encourage as an environmental protection in order to minimize waste material and as a construction cost reduction measure. It can be observed that the highest rate of water absorption of the brick was in 30% replacement while the lowest water absorption obtained in 20% replacement of rice husk. On the hand, it can be observed that the highest rate of density test of the brick was in 20% replacement while the lowest density test obtained in 30% replacement of rice husk. The results revealed that the strength factor, compressive strength and flexural strength of the sand brick increased as the percentage replacement of sand with rice husk increased except 30% ratio of rice husk replaced. Conclusively, 20% of Rice Husk is the best recommended amount to be used as partial sand replacement to produced sand brick with better strength.